2015
DOI: 10.1590/s1980-65742015000300009
|View full text |Cite
|
Sign up to set email alerts
|

The period of the day affects the twenty-four hour blood pressure response to an acute combined exercise session in Brazilian jiu jitsu athletes

Abstract: The purpose of this study was to compare the effect of a combined exercise session performed at different periods of the day on the 24h blood pressure (BP) response. Anaerobic threshold (AT) and 12 repetition maximum (12RM) tests were evaluated in nine Brazilian jiu-jitsu athletes (male) (22±3.7 y; 176±5.0 cm; 73.4±9.7 kg; 6.8±2.1 % body fat). Four experimental sessions were performed: resistance exercise followed by aerobic exercise [Morning (MornS) and Afternoon (AfternS)] and Control (C) [Morning and Aftern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…However, those studies measured VO 2max during treadmill tests, a condition that does not occur during matches. The remaining studies (six in total) utilized indirect methods to predict the athletes’ VO 2max [ 1 , 16 , 35 – 38 ]. Additionally, no studies have been found that investigated the aerobic profile of female athletes in Brazilian jiu-jitsu.…”
Section: Discussionmentioning
confidence: 99%
“…However, those studies measured VO 2max during treadmill tests, a condition that does not occur during matches. The remaining studies (six in total) utilized indirect methods to predict the athletes’ VO 2max [ 1 , 16 , 35 – 38 ]. Additionally, no studies have been found that investigated the aerobic profile of female athletes in Brazilian jiu-jitsu.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, Moreira et al [4] demonstrated that, during jiu-jitsu competitions, there is a significant increase in plasma cortisol concentration, which can contribute to altering the blood pressure (BP) of the fighters [5,6]. However, in inexperienced athletes in the adult category (aged 18-29 years), a reduction in systolic blood pressure (SBP) is observed after the end of simulated jiu-jitsu matches [7,8].…”
Section: Introductionmentioning
confidence: 99%